NETWORK OF INFORMAL TOURISM EDUCATION ORGANIZATIONS IN PARE ENGLISH VILLAGE - Yogi Yunanto (Media Mahardhika, 2023)
The learning model is a strategy used by teachers to increase learning motivation, learning attitudes among students, able to think critically, have social skills, and achieve more optimal learning outcomes. Referring to this, the development of learning models continues to change from traditional models to more modern models. Researchers used the ethnographic method during a pandemic for six months, January-June 2020. This method was considered appropriate to obtain data on the lives and actions of a group in certain situations in society from the point of view of their culture of life. The data collection process, both primary and secondary, is carried out continuously. Based on the results of the research, it can be concluded that there are several things that support the success of students studying at English language educational institutions in Pare. The learning method is one of the supporting factors. For this reason, the method used is the 'Boarding Teaching' and 'In Class Scheduled' methods. These two methods are carried out by carrying the concept of 'fun teaching' or an interesting method that does not seem too formal and rigid. By using this kind of method students become more interested and enthusiastic to learn. In fact, the point is that the learning that is carried out focuses on practice, because English is a skill, not just knowledge. In general, the learning model carried out in English language education institutions in Pare is a similar method, namely the 'Fun Englsih' method, which is learning English in a pleasant environmental situation and games that are usually carried out to train students to use English and make it easier for students remember the material being taught such as vocabulary and expressions in English. Another method used is group discussion or group discussion.